Evaluation of vegetable pigeonpea [Cajanus cajan (L.) Millsp] genotypes for yield stability - J. D. Ojwang; R. Nyankanga; N. V. P. R. G. Ganga Rao; J. Imungi (CABI Agriculture and Bioscience)
Abstract Background Vegetable pigeonpea is an important food security crop in the marginal dry areas of the Eastern region of Kenya. The adaptation and stability of vegetable pigeonpea genotypes across different agro-ecological zones in Kenya are not adequately determined. The objective of this study was to evaluate the yield stability and adaptability of genotypes: KAT 60/8, MZ 2/9, ICEAP 00554, ICEAP 00557 and KIONZA based on additive main effects and multiplicative interactions (AMMI) and Genotype plus genotype by environment (GGE biplot) analysis. Methods Evaluation of vegetable pigeonpea Genotypes was conducted at Kiboko, Katumani and Kambi ya Mawe research stations located in Eastern region and University of Nairobi Field station in central region of Kenya. The genotypes were planted in a Randomized Complete Block design (RCBD), replicated three times at all sites. Rainfall at Kiboko and Kabete were supplemented with irrigation, using sprinklers, for a total of 38 times, providing 832 mm of water. The crop was protected from pests by the application of broad-spectrum, non-systemic, pyrethroid alpha-cypermethrin and dimethoate, after field scouting. All other agronomic and cultural practices were done as recommended for each location. Results Combined analysis of variance (ANOVA) at six environments revealed highly significant (P  < 0.01) variations in G × E interactions for yield (Kg/ha), 100 Seed mass (g/100 seed), days to flower and maturity (P  < 0.05). AMMI model for grain yield interaction principal components analysis (IPCA), explained 96.5% of the total yield variation. The cultivar MZ 2/9 and KAT 60/8 recorded a lower IPCA1, indicating a wider adaptation and stability. Kambi ya Mawe, Katumani and Kiboko had higher IPCA1, indicating greatest interactive environments and adapted genotypes. Kambi ya Mawe, was the most ideal location for evaluating pigeonpea genotypes. While KIONZA was the most ideal genotype for yield performance, MZ 2/9 and KAT 60/8 were most stable with a wider adaptation. Conclusion KIONZA should be used as a reference genotype, while Kambi ya Mawe would be the most ideal location for testing the vegetable pigeonpea genotypes in breeding research. Increased deployment of stable pigeon pea cultivars, MZ 2/9 and KAT 60/8 would enhance food security in the dry areas of Eastern regions of Kenya. These genotypes need to be promoted with farmers for wider adoption in the Eastern region of Kenya.